External Validation of Two Models to Predict Delirium in Critically Ill Adults Using Either the Confusion Assessment Method-ICU or the Intensive Care Delirium Screening Checklist for Delirium Assessment. Issue 10 (October 2019) - Wassenaar, Annelies; Schoonhoven, Lisette; Devlin, John W.; van Haren, Frank M. P.; Slooter, Arjen J. C.; Jorens, Philippe G.; van der Jagt, Mathieu; Simons, Koen S.; Egerod, Ingrid; Burry, Lisa D.; Beishuizen, Albertus; Matos, Joaquim; et al.
Abstract : Objectives: To externally validate two delirium prediction models (early prediction model for ICU delirium and recalibrated prediction model for ICU delirium) using either the Confusion Assessment Method-ICU or the Intensive Care Delirium Screening Checklist for delirium assessment. Design: Prospective, multinational cohort study. Setting: Eleven ICUs from seven countries in three continents. Patients: Consecutive, delirium-free adults admitted to the ICU for greater than or equal to 6 hours in whom delirium could be reliably assessed. Interventions: None. Measurements and Main Results: The predictors included in each model were collected at the time of ICU admission (early prediction model for ICU delirium) or within 24 hours of ICU admission (recalibrated prediction model for ICU delirium). Delirium was assessed using the Confusion Assessment Method-ICU or the Intensive Care Delirium Screening Checklist. Discrimination was determined using the area under the receiver operating characteristic curve. The predictive performance was determined for the Confusion Assessment Method-ICU and Intensive Care Delirium Screening Checklist cohort, and compared with both prediction models' original reported performance. A total of 1, 286 Confusion Assessment Method-ICU–assessed patients and 892 Intensive Care Delirium Screening Checklist–assessed patients were included. Compared with the area under the receiver operating characteristic curve of 0.75 (95% CI, 0.71–0.79) in the original study, the area under the receiver operating characteristic curve of the early prediction model for ICU delirium was 0.67 (95% CI, 0.64–0.71) for delirium as assessed using the Confusion Assessment Method-ICU and 0.70 (95% CI, 0.66–0.74) using the Intensive Care Delirium Screening Checklist. Compared with the original area under the receiver operating characteristic curve of 0.77 (95% CI, 0.74–0.79), the area under the receiver operating characteristic curve of the recalibrated prediction model for ICU delirium was 0.75 (95% CI, 0.72–0.78) for assessing delirium using the Confusion Assessment Method-ICU and 0.71 (95% CI, 0.67–0.75) using the Intensive Care Delirium Screening Checklist. Conclusions: Both the early prediction model for ICU delirium and recalibrated prediction model for ICU delirium are externally validated using either the Confusion Assessment Method-ICU or the Intensive Care Delirium Screening Checklist for delirium assessment. Per delirium prediction model, both assessment tools showed a similar moderate-to-good statistical performance. These results support the use of either the early prediction model for ICU delirium or recalibrated prediction model for ICU delirium in ICUs around the world regardless of whether delirium is evaluated with the Confusion Assessment Method-ICU or Intensive Care Delirium Screening Checklist. Abstract : Supplemental Digital Content is available in the text.